Pregnancy as an Agent to Neutralize Painting as a Gender-Biased Concept in Contemporary China — The Works of Yu Hong, Ji Jingning and Xu Hualing - Zhang, Tong (Art and Society, 2025)
This article offers a brief inquiry into pregnancy as a theme of contemporary art in the West and China. It subsequently tracks the entrenched frameworks of painting in China and the neglect of pregnancy as a theme in the Chinese art world from the historical perspective, in order to navigate pregnancy-themed paintings by three selected female artists: Yu Hong, Ji Jingning, and Xu Hualing. Through analyzing their paintings, it concludes that these pieces not only increase the visibility of women’s self-perception during pregnancy but also aestheticize pregnancy as a subject within their respective artistic traditions.